Emotional Intelligence and its Relationship to Life Satisfaction among Secondary School Female Students in Hail region - Al-Shammari, Amani Abdullah Aqla (Journal of Educational and Psychological Sciences, 2023)
This study aimed to identify the relationship between emotional intelligence and life satisfaction among female high school students. The study followed a descriptive correlational methodology and the sample consisted of 145 students, selected using stratified random sampling. The study tools included: the Emotional Intelligence Scale prepared by Al-Khawli (2002) and the Life Satisfaction Scale translated and standardized by Al-Dosari (2022). The study results showed a positive and statistically significant correlation between emotional intelligence and life satisfaction among female high school students in the Hail city. Based on the study results, a set of recommendations were formulated, including: activating the role of student counseling to develop life satisfaction among female high school students, the necessity of preparing counseling and preventive programs to detect and treat psychological and behavioral problems early among female high school students, and encouraging students to participate in various social activities, which positively reflects on their evaluation of different aspects of their lives and increases their satisfaction with them.
Keywords: Emotional Intelligence; Satisfaction with Life; Secondary School Students; Hail Region